Perception of young adults about aging (Research, Society and Development, 2021)
Plants with medicinal purposes are part of the great biodiversity, and are introduced in the life of the population since the most Aging is understood to be part of the natural process of human development, which brings changes both physically and psychically. In addition to being biological, inherent and inevitable, it is also culturally constructed, and the environment in which you live can influence the perception of people in a certain society and culture. Therefore, the objective was to identify the perception of young adults about the aging process, and as specific objectives to characterize the sample in relation to the sociodemographic profile; investigating the acceptance of aging itself, as well as the knowledge and positioning of the sample in relation to the rights of the elderly. It is field research, descriptive, quantitative, and carried out online with a sample of 240 participants. As a tool, a semi-structured questionnaire was used, and the results were processed using the SPSS. This study followed all the ethical guidelines of the Resolution 466/12. Most participants perceived aging as a positive stage of life. They were not afraid of getting old. Also, they were prone to know and agree with the Public Policies of the elderly. n this way, there is a change in the negative and stereotyped view that society has historically presented in relation to the elderly, giving rise to a more positive and natural understanding of old age.